EZH2 inhibitors: a patent review (2014-2016). (3rd July 2017) - Stazi, Giulia; Zwergel, Clemens; Mai, Antonello; Valente, Sergio
ABSTRACT: Introduction : The histone methyltransferase EZH2 is the catalytic subunit of the PRC2 complex involved in H3K27 trimethylation. Aberrant PRC2 activity has been reported in several cancers and EZH2 overexpression has been associated with poor outcome in different tumors. EZH2 somatic mutations and deletions was found in lymphomas, myelodysplastic and myeloproliferative disorders and associated with higher H3K27me3 levels. Numerous chemical entities have been studied as EZH2 inhibitors in the recent years and some of them entered the cancer clinical arena. Areas covered : This review summarizes recent efforts in the drug development of EZH2 inhibitors reported in the patent literature covering the 2014–2016 period, and their potential use as therapeutics mainly in cancerous diseases. Expert opinion : Despite the number of compounds described, only a few of them entered the clinical arena. Moreover, most of the compounds developed share a common 2-pyridone ring pharmacophore. Recently, secondary mutants have been described to be resistant to the standard EZH2 inhibitors treatment. Based on these data a lot of effort is still required to find new chemical entities that inhibit EZH2 directly, or indirectly (via PRC2 disruption). Several issues are still to be settled, such as drug resistance and the importance of selectivity over EZH1 or somatic EZH2 mutants.